Developing English reading material for midwifery students in Madura Islamic University - setiyawan, arisandi; Yunitaka, B, Dinar Vincy (Lingual Journal of Language and Culture; Vol 10 No 2 (2020): Lingual: Journal of Language and CultureDO - 10.24843/LJLC.2020.v10.i02.p01, 2020)
This study was conducted to develop English reading material for midwifery student in Madura Islamic University. The aim was to help students to enrich their experience, build their knowledge, and construct their reading comprehension especially in midwifery context. The procedures of doing the development of this research ( R and D )  were  include of need analysis, material development, expert validation, revision, field testing and final product. To collect the relevant information, the instrument used in this study was need analysis that consist of questionnaires, and interview guide. The information that was gotten from need analysis becomes a basis for developing the reading material. Moreover, Contextual Teaching and Learning strategy was used by the researchers in developing reading material, then the expert validators was carry out to evaluate the material. After revising based on the experts’ suggestion, the next step was field testing, it was done to know the applicability of material development. Finally, the final product of this study consists of ten chapters about reading material which is suitable for the midwifery context.